(untitled) (World Conference on Social Sciences, Law and Public Policy, 2026)
The economic burden of acute calculous cholecystitis is substantial: in-hospital costs are driven primarily by duration of stay, rates of conversion from laparoscopic to open surgery, postoperative complications requiring re-intervention, and unplanned 30-day readmissions [1]. In middle-income settings such as Uzbekistan, a further component is extended temporary work incapacity and, in complicated cases, permanent disability, which generate indirect costs rarely captured in clinical trial outcome sets but directly relevant to national health economic assessments. Any surgical decision protocol that consistently reduces complications and shortens hospitalisation is potentially cost-saving, even if it introduces an upstream diagnostic expenditure.